Meeting the Rudd Government's equity targets for universities: three scenarios - Phillimore, John; Koshy, Paul (Centre for Population and Urban Research, Monash University, 2010)
The Rudd Government has outlined a goal that by 2025, 40 per cent of Australians aged 25 to 34 should hold a Bachelor 's level qualification and that, by 2020, around 20 per cent of undergraduate enrolments at Australian universities should be filled by students from low socio- economic-status (SES) backgrounds. The current level of low SES participation is 16.3 per cent, with substantial diversity in outcomes between institutional groupings and states and territories. This paper considers three policy options for raising national participation levels of students from low SES backgrounds: (i) uniform increases across all institutions to meet the 20 per cent national target; (ii) differential increases in indirect proportion to current levels of low SES participation by institutions; and (iii) differential increases proportional to the share of the low SES population located within each state and territory. The authors find that a national approach to achieving the 20 per cent target needs to consider both current enrolment patterns across institutional groupings as well as differences in the low SES population across the states and territories. Students' SES is currently determined by their postcode. The authors argue that this is unsatisfactory and that better measures must be developed before targets can be set for individual institutions.